Pengaruh Lingkungan Kerja dan Disiplin Kerja Terhadap Retensi Karyawan pada PT Brougue Barbershop Indonesia - Hannani, Ganda Anugrah; Susita, Dewi; Parimita, Widya (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the effect of work environment and work discipline on employee retention at PT Brogue Barbershop Indonesia. The research uses a quantitative approach with a survey method. The population of this study includes all permanent employees of PT Brogue Barbershop Indonesia. A saturated sampling technique was applied, in which all members of the population were selected as respondents, resulting in a total of 60 respondents. Data were collected using a questionnaire with a 1–4 Likert scale. The collected data were analyzed using multiple linear regression with the assistance of SPSS version 29. The results indicate that the work environment has a positive and significant effect on employee retention at PT Brogue Barbershop Indonesia. Work discipline also has a positive and significant effect on employee retention. Simultaneously, work environment and work discipline significantly influence employee retention.